WILAYATUL HISBAH & SYARIAT ISLAM DI ACEH: Tinjauan Wewenang dan Legalitas Hukum - Bahri, Samsul (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-undangan, Ekonomi Islam, 2017)
Legality in the implementation of  a  rule or Qanun is very important to avoid actions that violate the law. Aceh in the course of time tried to improve the implementation of sharia law by ratifying several qanuns of sharia. With the increase of  those  qanuns,  certainly it  will  give some  changes  to  the authority  of  Wilayatul  Hisbah  (WH)  institution  in  the supervision and the action against the violation of Islamic Sharia  in  Aceh,  especially  after  the  enactment  of  Aceh Qanun no. 7 in 2013 on the procedural of Islamic Criminal Law and Aceh Qanun no. 6 in 2014 on Criminal Law. This article  tries  to  describe  the  development  of  of  the implementation  of  Islamic  law  with  an  account  on Wilayatul  Hisbah  in  the  record  of  history  till  the contemporary situation from the aspects of law sources and it?s authority in the enforcement of Sharia law.